Assessing the Larvicidal Properties of Endemic Campeche, Mexico Plant Piper cordoncillo var. apazoteanum (Piperaceae) against Aedes aegypti (Diptera: Culicidae) Mosquitoes - Nancy Alonso-Hernández; Carlos Granados-Echegoyen; Ileana Vera-Reyes; Rafael Pérez-Pacheco; Fabián Arroyo-Balán; Alejandro Valdez-Calderón; Arián Espinosa-Roa; Henry Jesús Loeza-Concha; Evert Villanueva-Sánchez; Florinda García-Pérez; Fidel Diego-Nava (Insects, 2023)
The research aims to investigate the mortality effect of essential oil from Piper cordoncillo var. apazoteanum, an endemic plant from Campeche, Mexico, on early second-instar Aedes aegypti larvae; it also aims to identify the volatile compounds present in the fresh leaves of the plant. To test the effectiveness of the essential oil, we followed World Health Organization Standard Procedures. Larvae were observed for 17 consecutive days after treatment to determine the mortality and growth-inhibitory effect exerted by the essential oil. The results showed that the essential oil was effective in controlling mosquito populations. At a concentration of 800 ppm, the oil achieved an effectiveness rate of 70.00 ± 8.16% after 24 h, increasing to 100.00 ± 0.01% mortality after 72 h. With a concentration of 400 ppm, the effectiveness was 98.33 ± 0.17% by the end of the experiment. Furthermore, the obtained results demonstrated that the LC50 value was 61.84 ± 6.79 ppm, while the LC90 value was 167.20 ± 11.49 ppm. Essential oil concentrations inhibited the growth of immature insect stages, with concentrations between 800–100 ppm demonstrating very high inhibitory activity, and the lowest concentration of 50 ppm showing high inhibitory activity. The study also identified 24 chemical compounds representing 86.71% of the volatile compound composition of the fresh leaves of P. cordoncillo; the most abundant compounds were Safrole, Caryophyllene oxide, E-Nerolidol, and Calarene epoxide. The method used to extract the volatile compounds, solvent-free microwave extraction (SFME), is a promising alternative to traditional methods that avoids the use of potentially harmful solvents, making it more ecologically friendly and potentially safer for professionals handling the extracted compounds. Overall, the study demonstrates the potential of P. cordoncillo essential oil as an effective means of controlling mosquito populations, and provides valuable information on the chemical composition of the plant.Moreover, our study is the first to report on the biological activity and chemical composition of P. cordoncillo worldwide.